'Somehow This Whole Process Became so Artificial': Exploring the Transitional Justice Implementation Gap in Uganda. (26th April 2019) - Macdonald, Anna
Abstract ∞ : This article explores a key challenge in contemporary international efforts to promote transitional justice (TJ) in nontransitioning, conflict-affected states: the 'implementation gap, ' in which policies are designed and funded but neither enacted nor implemented. Findings based on long-term qualitative fieldwork in Uganda indicate the implementation gap is co-constituted by technocratic donor approaches and domestic elite political maneuvering in a semi-authoritarian regime. The interaction between the two produces two forms of political artifice: 'isomorphic mimicry' and 'calculated stasis, ' which stall the emergence of substantive TJ reform. Findings are relevant to the wide range of nontransitioning contexts where TJ is promoted by international donors and have important implications for its claimed potential to catalyze or restore civic trust in political systems in the aftermath of massive human rights violations.